2013
DOI: 10.1007/978-3-642-40498-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Finger on the Pulse: The Value of the Activity Stream in the Enterprise

Abstract: Abstract. The activity stream, which syndicates user activities across social media, has been gaining popularity on the web. With social media infiltrating the enterprise and higher portions of the workforce becoming accustomed to consuming information through activity streams, it also has the potential to play a key role in shaping the workplace. This work provides a first comprehensive study of an enterprise activity stream. We analyze different characteristics of the stream, its usage through a faceted sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, papers explore how users search, filter and interact with activity streams. Guy et al (2013) demonstrated activity streams can pose a new way of searching for information, as it is used to filter than search for information. The feature is used for a variety of purposes, like getting a sense of what colleagues do, to track recent project activities of individuals or groups, search for recent news, and latest updates in discussion, etc.…”
Section: Research Stream 1: It Companies and Proprietary Esmpsmentioning
confidence: 99%
“…For example, papers explore how users search, filter and interact with activity streams. Guy et al (2013) demonstrated activity streams can pose a new way of searching for information, as it is used to filter than search for information. The feature is used for a variety of purposes, like getting a sense of what colleagues do, to track recent project activities of individuals or groups, search for recent news, and latest updates in discussion, etc.…”
Section: Research Stream 1: It Companies and Proprietary Esmpsmentioning
confidence: 99%
“…Recently, there has been an emphasis by enterprises to develop and adopt socialsoftware platforms for use within the enterprise, enabling employees to keep up to date across the enterprise. These platforms have many benefits for the enterprise (Guy, Steier, Barnea, Ronen, & Daniel, 2013) (Marlow & Dabbish, 2014).…”
Section: Social Software and Social Networkingmentioning
confidence: 99%